Formalin-free fixation and xylene-free tissue processing preserves cell-hydrogel interactions for histological evaluation of 3D calcium alginate tissue engineered constructs - Da Silva, Iran Augusto; Gvazava, Nika; Putra Wendi, Indra; Guinea, Rodrigo; García Giménez, Francisco; Stegmayr, John; Klementieva, Oxana; Wagner, Darcy E. (Frontiers in Biomaterials Science, 2023)
Histological evaluation of tissue- engineered products, including hydrogels for cellular encapsulation, is a critical and invaluable tool for assessing the product across multiple stages of its lifecycle from manufacture to implantation. However, many tissue- engineered products are comprised of polymers and hydrogels which are not optimized for use with conventional methods of tissue fixation and histological processing. Routine histology utilizes a combination of chemical fixatives, such as formaldehyde, and solvents such as xylene which have been optimized for use with native biological tissues due to their high protein and lipid content. Previous work has highlighted the challenges associated with processing hydrogels for routine histology due to their high water content and lack of diverse chemical moieties amenable for tissue fixation with traditional fixatives. Thus, hydrogel-based tissue engineering products are prone to histological artifacts during their validation which can lead to challenges in correctly interpreting results. In addition, chemicals used in conventional histological approaches are associated with significant health and environmental concerns due to their toxicity and there is thus an urgent need to identify suitable replacements. Here we use a multifactorial design of experiments approach to identify processing parameters capable of preserving cell-biomaterial interactions in a prototypical hydrogel system: ionically crosslinked calcium alginate. We identify a formalin free fixative which better retains cell-biomaterial interactions and calcium alginate hydrogel integrity as compared to the state-of-the-art formalin-based approaches. In addition, we demonstrate that this approach is compatible with a diversity of manufacturing techniques used to fabricate calcium alginate-based scaffolds for tissue engineering and cell therapy, including histological evaluation of cellular encapsulation in 3D tubes and thin tissue engineering scaffolds (~50 μm). Furthermore, we show that formalin- free fixation can be used to retain cell-biomaterial interactions and hydrogel architecture in hybrid alginate-gelatin based scaffolds for use with histology and scanning electron microscopy. Taken together, these findings are a significant step forwards towards improving histological evaluation of ionically crosslinked calcium alginate hydrogels and help make their validation less toxic, thus more environmentally friendly and sustainable.